The Influence of Mathematical Creative Thinking Ability on Students' Self-Regulated Learning Through a Scientific Approach - Mubarika, Melinda Putri; Faiqoh, Elok; Susilawati, Susilawati; Raharjo, Totok Dwi; Yaniawati, Poppy (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
The purpose of this study was to improve the ability of creative thinking, to see the picture of self-regulated learning, and to analyze the effect of creative thinking ability on self-regulated learning through the implementation of the Scientific approach. This research method is a mixed method of insertion type. The research instrument used was a creative thinking ability test, observation, self-regulated learning scale, and interviews. The population in this study were students in a private high school in Bandung with a sample of 2 classes. The increase in creative thinking skills was analyzed by normalized gain scores, the description of self-regulated learning was analyzed by Post Hoc Tests, while the effect of creative thinking skills on self-regulated learning was used regression analysis. The results showed that the increase in the creative thinking ability of students who received the Scientific approach was better than the students who received conventional learning, there was no difference in the self-regulated learning of students who received learning using the Scientific approach and conventional models, and there was no difference the effect of creative thinking ability on self-regulated learning in learning with scientific approaches, and conventional ones.Tujuan penelitian ini adalah untuk meningkatkan kemampuan berfikir kreatif, melihat gambaran kemandirian belajar, dan menganalisis pengaruh kemampuan berfikir kreatif terhadap kemandirian belajar melalui implementasi pendekatan scientific. Penelitian ini menggunakan metode campuran tipe penyisipan. Instrumen penelitian yang digunakan adalah tes kemampuan berpikir kreatif, observasi, skala kemandirian belajar, dan wawancara. Populasi dalam penelitian ini adalah peserta didik di salah satu SMA swasta Bandung dengan sampel sebanyak 2 kelas. Peningkatan kemampuan berpikir kreatif dianalisis dengan skor gain ternormalisasi, gambaran kemandirian belajar dianalisis dengan Tes Post Hoc, sedangkan pengaruh kemampuan berpikir kreatif terhadap kemandirian belajar digunakan analisis regresi. Hasil penelitian menunjukkan bahwa peningkatan kemampuan berfikir kreatif peserta didik yang memperoleh pendekatan Scientific lebih baik daripada peserta didik yang memperoleh pembelajaran konvensional, tidak terdapat perbedaan kemandirian belajar peserta didik yang memperoleh pembelajaran dengan pendekatan Scientific maupun konvensional, serta tidak terdapat pengaruh kemampuan berfikir kreatif terhadap kemandirian belajar pada pembelajaran dengan pendekatan Scientific, maupun konvensional.